STRATEGI KOMUNIKASI PEMASARAN TATV DALAM UPAYA MEMPERKENALKAN PRODUK Chocomania - Setyawan, Agustinus (Transformasi, 2015)
Modern marketing is not just oriented in a way to develop a good product, and has appeal to invite public attention. In this study, researchers used the title